PERAN KEMAMPUAN DIGITAL DALAM MEMEDIASI PENGARUH TRANSFORMASI DIGITAL TERHADAP LITERASI DIGITAL: STUDI KOMPARATIF KARYAWAN PROYEK DAN NON-PROYEK PT WASKITA KARYA (PERSERO) TBK - Ilga Widya Panca; Endroyono (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
Digital transformation has become an important strategy in improving organizational competitiveness, including in the construction industry. However, its success greatly depends on the readiness of human resources to utilize technology effectively. This study aims to analyze the role of digital capabilities in mediating the influence of digital transformation on employee digital literacy, as well as to examine differences in these patterns of influence between project and non-project employees at PT Waskita Karya (Persero) Tbk. This study uses a quantitative approach with a survey method of 280 respondents consisting of project and non-project employees. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and Multi-Group Analysis (MGA). The results show that digital transformation has a positive and significant effect on employees' digital capabilities and digital literacy. Digital competence was found to play a partial mediating role in the relationship between digital transformation and digital literacy. Comparative analysis revealed differences in the patterns of influence between project and non-project employees. This study concludes that the impact of digital transformation on digital literacy works through the mechanism of digital competence and is influenced by the work context. These findings have implications for the development of more contextual strategies for improving digital competence in construction organizations. Keywords: Construction Industry, Digital Capabilities, Digital Literacy, Digital Transformation, Mediator.